THEORETICAL AND METHODOLOGICAL PRINCIPLES OF NETWORK TECHNOLOGIES USE IN THE SYSTEM OF CONTINUING EDUCATION - Velihovska, А.Б. (Journal of Information Technologies in Education (ITE), 2012)
Use of modern network technologies in the professional activity of teaching staff as one of the directions of modernization of the system of continuing education are considered in the article. It is also examined main directions of formining of network learning environment of In-Service Teachers’ Training Institute.